Word-Formation Process on COVID-19 Related Terms as Japanese Language Variation - Nadya Inda Syartanti (IZUMI, 2021)
This research aims to identify the types of vocabulary in Japanese, to explore the word-formation process, and to analyse the function of COVID-19 related terms conveyed by various content creators on YouTube channels, from Japan and Indonesia. The seven YouTube channel accounts are Aki no Sora (Indonesia), po.n.go_id or Pocket Nihongo (Indonesia), Sakura Pinku (Indonesia), Wagomu (Indonesia), Omoshiroi Nihongo (Japan), Japanese Ammo with Misa (Japan), and Coto Academy (Japan that used as the data source. Data were collected using the observation method and analysed by the distribution method. The results showed that the COVID-19 related terms are dominated by the type of vocabulary kango as the form or type of vocabulary that is most widely used in matching the COVID-19 related term. Among all word-formation processes, the COVID-19 terms in Japanese identified as borrowing, compounding, and multiple processes. However, the multiple word-formation processes are dominated on COVID-19 terms in Japanese. It related to the domination of the type of kango used. From that, there are multiple functions that are included in COVID-19 terms in Japanese, namely disease information, preventive action, symptom, and announcement. Therefore, this research can be contributed to data analysis, which used morphological analysis in Japanese terms.